EXAMINING POWERS THROUGH SURYANI’S REPRESENTATION AGAINST SEXUAL VIOLENCE IN WREGAS BHANUTEJA’S PHOTOCOPIER - Angjaya, Sonny; Muljadi, Hianly; Deborah, Joanna (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This study examines the representation of woman against sexual violence in Photocopier, an Indonesian film directed by Wregas Bhanuteja. In film, women as sexual violence victims are often misrepresented through stereotyping as the helpless victims who need men’s help to deal with the situation or showing extreme violence against their perpetrators to exact revenge. If not stereotyped, women as sexual violence victims also tend to be fetishized as their victimized body often sexualized for erotic pleasures. In its protagonist, Sur, Photocopier took different approach by representing the victim as a woman with powers to fight against the sexual violence she experienced. This study focuses in examining how Sur exerts her powers and how those powers impacted the sexual violence case that she experienced. The study is conducted qualitatively using content analysis method which examines the visual aspects as well as dialogues from the film and applying Amy Allen’s theory of feminist power relation. The analysis identifies that Suryani possesses and exercises all three types of feminist power posed by Allen, which are “power-to,” “power-over,” and “power-with,” as a sexual violence victim. The study reveals that while the film tries to represent Sur as a powerful woman, she is also adjacently represented as a stereotypical powerless sexual violence victim who is helpless to fight against her perpetrators even after exercising all her powers both personally and collectively. However, such stereotypical representation may be necessary to show the reality of sexual violence victims and as a form of criticism against the mishandling of sexual violence case.